Pengaruh Lingkungan Kerja Dan Motivasi Terhadap Kinerja Fasilitator Program Peningkatan Kualitas Kawasan Permukiman (P2KKP) - Takwim (Jayapangus Press, 2019)
This study aims to examine and analyze the Effect of Work Environment and Motivation on the Performance of Program Facilitator of Quality Improvement of Settlement Area (P2KKP) in Kendari City, Southeast Sulawesi Province. This research uses descriptive quantitative research design. This study aims to analyze the Effect of Work Environment and Motivation on the Performance of Program Facilitator of Quality Improvement of Settlement Area (P2KKP) in Kendari City, Southeast Sulawesi Province with indicators of the assessment of the work environment: the physical environment, the spicological environment and the motivational indicators: the need for achievement, the need for recognition, the sense of responsibility, the need for progress, the work itself, and the performance indicators: completing the work on time, showing skills / skills at work, demonstrate creativity and work initiatives, meet / exceed quality and quantity of work targets. This study took a sample of 35 facilitators. The result of research shows that work environment and work motivation influence performance positively.